2015
DOI: 10.1002/ar.23185
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Secondary Follicle Characteristics, Density, Activity, and Hoxc13 Expression Pattern of Hexi Cashmere Goats Breed

Abstract: This experiment was conducted to identify some aspects of secondary follicle (SF) characteristics of Hexi cashmere goats at five different growing stages in one year in order and discover the expression pattern of Hoxc13 in a SF cycling to provide morphological basis for studying the growth of cashmere. Ten cashmere goats of one-year old (5 males, 5 females) were included in this study. The density and activity of SF were observed and measured by making paraffin sections, the ultra-structural features of SF we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Data in Tables and revealed that the diameter, depth, density and activity of SF in both group of Longdong cashmere goat had a growing tendency in anagen stage. It was consistent with the study on Inner Mongolia Cashmere goat (Li et al, ) and Hexi cashmere goat (He et al, ). The difference was that the largest value of diameter, depth and activity of SF in extensively fed group presented in September, while the value of diameter, depth density and activity of SF presented in October.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Data in Tables and revealed that the diameter, depth, density and activity of SF in both group of Longdong cashmere goat had a growing tendency in anagen stage. It was consistent with the study on Inner Mongolia Cashmere goat (Li et al, ) and Hexi cashmere goat (He et al, ). The difference was that the largest value of diameter, depth and activity of SF in extensively fed group presented in September, while the value of diameter, depth density and activity of SF presented in October.…”
Section: Discussionsupporting
confidence: 92%
“…Wu et al () found that the activity of hair follicle was highly correlated with the expression of Hoxc13 gene. The research of SF in Hexi cashmere goat have also found that the activity changes of SF and the expression of Hoxc13 are closely related (He et al, ). HSP can be detected in all organisms (Kakobsson et al, ; Zhang et al, 2014; Gautam et al, ; Murphy 2013).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The homeobox genes HOXC12 and HOXC13 genes identified in Sebei are involved in the anterior/posterior pattern specification (GO:0009952). The genes play a role in hair follicle differentiation, growth, and development by regulating the keratin differentiation-specific genes ( Wu et al, 2009 ; Taye et al, 2017 ). The HOXC13 gene has been reported to influence skin thickness.…”
Section: Discussionmentioning
confidence: 99%